PERANCANGAN TVC AGROEDUKASI DAN BUDIDAYA TANAMAN STROBERI BERSAMA ULTRA MILK DI DESA WISATA LEBAKMUNCANG CIWIDEY DALAM MENINGKATKAN RECOGNITION UNTUK KELUARGA MUDA - Fizky Anggadibya, Andika; Syafikarani, Aisyi; Agung Rangga Lawe, I Gusti (eProceedings of Art & Design, 2024)
opinions about educational activities, and their preferences for the Ultra M ilk brand. Theresults show that the majority of children consider the educational tourism experience in the strawberry garden to be interesting and educative. They also tend to prefer TV adsthat are short and to the point. However, further research is still needed to understand in more depth how promotional and educational concepts can more effectively reach and influence young families as potential consumers. Keywords: destination branding, holiday destinations, Ciwidey, education park